Mortality and major adverse cardiac events in women with breast cancer receiving radiotherapy: a 10-year cohort study of patients and population controls. (3rd October 2022) - Jacobs, J; L'hoyes, W; Lauwens, L; Weltens, C; Voigt, J U; Wildiers, H; Neven, P; Herrmann, J; Thijs, L; Staessen, J; Janssens, S; Van Aelst, L
Abstract: Background: Treatment for breast cancer (BC) frequently involves radiotherapy. Guidelines recommend screening for cardiac adverse events starting 10 years after radiotherapy. The rationale for recommending this interval is unclear and informed the objective of this study. Objectives: Study cardiovascular event rates in the first decade following curative radiotherapy for breast cancer, the time frame before guidelines recommend screening. Methods: We performed a monocentric, retrospective study enrolling all women with unilateral BC in 2007–2008, who received radiotherapy as part of their curative treatment. We compared event rates during 10 years follow-up with an age and risk factor-matched control population (FLEMENGHO population). Results: We included 1095 BC patients (median age 55y, IQR: 47–66y). Two hundred and eighteen (19.9%) women died. Cancer and cardiovascular mortality accounted for 107 (49.1%) and 22 (10.1%) deaths, respectively. The incidence of coronary artery disease was similar compared to age and risk-matched women [risk ratio 0.75 (95% CI 0.48–1.18)], yet heart failure (HF) [risk ratio 1.97 (95% CI 1.19–3.25)] and atrial fibrillation or flutter (AF) (risk ratio 1.82 (95% CI 1.07–3.08) occurred more often. Age [HR 1.040 (95% CI 1.012–1.069)], tumor grade [HR 1.646 (95% CI 1.103–2.458)], and neo-adjuvant treatment setting [HR 3.079 (95% CI 1.432–6.620)] were risk factors for mortality; hormonal therapy [HR 0.007 (95% CI 0.001–0.042)] proved protective. Risk factors for MACE were mean heart dose [HR 1.079 (95% CI 1.012–1.151], hormonal therapy, history of cardiovascular disease [HR 2.771 (95% CI 1.253–6.126)], and Mayo Clinic Cardiotoxicity Risk Score [HR 2.547 (95% CI 1.538–4.217)]. While mean heart dose [HR 1.141 (95% CI 1.017–1.282)] and cardiovascular history [HR 3.374 (95% CI 1.259–9.043] clearly associated with new onset HF, only a trend towards higher AF burden with increasing mean heart dose could be observed. Conclusions: Ten-year mortality following curative treatment for unilateral BC was mainly cancer-related. HF and AF constituted significantly increased risks in the first decade following irradiation. Mean heart dose, pre-existing cardiovascular diseases, and Mayo Clinic Cardiotoxicity Risk Score were risk factors for early cardiac mortality and adverse events and should guide early dedicated cardio-oncological follow-up. Funding Acknowledgement: Type of funding sources: None.